TEA INDUSTRY IN INDIA: REGION-WISE ANALYSIS - R. SIVANESAN (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
The commodities are classified into food and non-food items. The food items includes cereals (rice; wheat; maize and products) milk and milk products (milk liquid; baby food; ghee; butter), pulses (arhar; gram; moong; magoor and urad), Vegetables (potato; onion; pumpkin; bitter; gourd and patal) fruits and nuts banana; water melon; orange; mango; litchi; apple; grapes; and other fresh fruits; ground nut; cashew nut; kishmish and other dry fruits), salt and spices (salt iodized; salt others; chilli; black pepper; turmeric; gartic; ginger; curry power and other spices), sugar, (sugar crystal; gur; honey and other sugar item), Beverages and processed food (tea leaf; tea dust; coffee powders cold beverage and other beverages; biscuits and confectionary; pickles; jam-jelly and other processed foods) . In the category of beverages and processed food found tea is included. Tea is considered as important beverages in India. Tea provides the average Indian with a pleasant and stimulating non-alcoholic beverage at a reasonable affordable price and has found a place in the culture. Tea is one of the important fast moving consumer goods in India. This study analyses the Tea Industry with special reference to region-wise.